Design of high directional crossed dipole antenna with metallic sheets for UHF and VHF applications - Govardhani, I.; Venkata Narayana, M.; Navya, A.; Venkatesh, A.; Charles Spurjeon, S.; Sai Venkat, S.; Sanjay, S. (International Journal of Engineering and Technology, 2017)
A compact dual band cross dipole antenna surrounded with metallic plates at five sides has been proposed in this article. comparative analysis has been done between the dipole and cross dipole antenna. On comparing these two antennas the proposed antenna has the high gain of 7db and radiation efficiency of 95 percent. The peak directivity of the proposed antenna is 5DB and its front to back ration is 60. The return loss, gain, radiation patterns and co polarization and cross polarization of the antenna has been observed and analysed using AN-soft HFSS v13.The proposed antenna works at the range of 0.6GHz to 1.5GHz which covers the applications like GSM, GNSS and some of the applications which covers in the range of UHF and VHF.